PENGARUH KEBIJAKAN DIVIDEN, KEBIJAKAN HUTANG, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Manufaktur Sektor Aneka Industri yang Terdaftar di BEI Periode 2015-2017) - Siti Nur Laelatul Rohmah; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG)
ABSTRACT The purpose of this study was to determine the effect of dividend policy, debt policy, and company size on the value of the company in various industrial manufacturing companies. The independent variables in this study are dividend policy, debt policy, and firm size, while the dependent variable in this study is firm value. The type of research used is empirical research with the data used, namely secondary data obtained by searching and collecting annual report data obtained from the website www.idx.com. The population in this study is the various industrial sector manufacturing companies listed on the Indonesia Stock Exchange in the period 2015-2017 with a total of 43 companies. The sample selection technique in this study was using purposive sampling, so that a sample of 16 companies was obtained. To solve the problem in this study, using the research method of multiple regression analysis. The results of data analysis show that: There is a positive influence on the dividend policy variable on firm value while the debt policy and company size have a negative effect on Company Value in various industrial sector manufacturing companies. Keywords: Dividend Policy, Debt Policy, and Company Size Against Company Values